2013
DOI: 10.4103/2278-9626.116017
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effect of tobacco on resting whole mouth salivary flow rate and pH: An institutional based comparative study

Abstract: Background: Saliva is the first biological fluid that is exposed to tobacco and is responsible for its changes especially the salivary flow rate (SFR) and salivary pH. Aims and Objectives: The aim of this study was to analyze and compare the long-term effects of tobacco on SFR and pH between tobacco chewers, smokers, and controls. Materials and Methods: A total of 60 Subjects were divided equally into tobacco smokers (group A), chewers (group B), and controls (group C). Saliva of each subject was collected und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 11 publications
2
24
0
3
Order By: Relevance
“…The chronic effects of cigarette use on flow rate are still unclear. While some studies [ 15 , 17 ] reported a decrease of ECS flow rate when compared to non-smokers, another study [ 2 ] showed similar results between the two groups. This study supports the absence of effect of WTS on flow rate.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…The chronic effects of cigarette use on flow rate are still unclear. While some studies [ 15 , 17 ] reported a decrease of ECS flow rate when compared to non-smokers, another study [ 2 ] showed similar results between the two groups. This study supports the absence of effect of WTS on flow rate.…”
Section: Discussionmentioning
confidence: 91%
“…Moreover, the effects of cigarette smoking on the above data have also been rarely evaluated in the literature. [ 2 , 13 – 17 ]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, Al Taee in 2010 did not find significant difference of pH between genders. 4,10,11 The saliva flow also eliminates carbohydrates timely which if metabolized by oral bacteriacan result in acid production altering oral pH. With the rise of salivary flow rate, it has been found that bicarbonate concentration also markedly increases.…”
Section: Evaluation Of the Salivary Flow Rate And Ph In Patients Withmentioning
confidence: 99%